Constrained Gazelles : High Potentials in West Africa's Informal Economy - Grimm, Michael; Knorringa, Peter; Lay, Jann (World Bank, Washington, DC, 2017)
The informal sector is typically characterized as being very heterogeneous and possibly composed of two clearly distinct segments, sometimes called the lower and upper tier. However, empirical evidence shows that even among lower tier entrepreneur's profitability can be quite high. The authors combine these findings and develop an innovative approach to identify what is called constrained gazelles, next to the well-known survivalists in the lower tier and growth-oriented top-performers in the upper tier. The sample of informal entrepreneurs in seven West-African countries allows linking the relative size of these three groups to the structural and macroeconomic environment in these countries.